Simplified Model Predictive Current Control of a Mono-Inverter Dual Parallel Permanent Magnet Synchronous Motors - Lee, Hyung Woo; Lee, Kyo Beum (2024 IEEE Energy Conversion Congress and Exposition, ECCE 2024 - Proceedings, 2024)
This paper proposes the simplified model predictive current control (MPCC) of a mono-inverter dual parallel (MIDP) permanent magnet synchronous motors (PMSMs). In the proposed MPCC method, one of the two parallel PMSMs is selected as the master PMSM to be object of control. The output torque of the slave PMSM is controlled with the master PMSM by utilizing the current relationship between the two motors. The application of the MPCC is operated through the d-axis current of the master PMSM. The candidate voltage vectors are generated within a segmented voltage vector plane for the reduction of computational burden and improvement of torque quality. To reduce the torque ripple, the voltage vectors applied to the inverter are conclusively determined using discrete space vector modulation (DSVM). The validity of the proposed method is verified through simulation results.
Keywords: current; Dual permanent magnet synchronous motor drive; Model predictive; Model predictive current control; Mono-inverter; Permanent Magnet Synchronous Motor; Permanent-magnet synchronous motor drives; Predictive current control; Surface mounted permanent magnet synchronous motor; Voltage vectors; Dual PMSM drive; Model predictive current control; Mono-inverter; Surface-mounted permanent magnet synchronous motor